The Interactive Effects of Fruit Intake Frequency and Serum miR-484 Levels as Biomarkers for Incident Type 2 Diabetes in a Prospective Cohort of the Spanish Adult Population: The Di@bet.es Study - Ana Lago-Sampedro; Wasima Oualla-Bachiri; Cristina Maldonado-Araque; Sergio Valdés; Inmaculada González-Molero; Viyey Doulatram-Gamgaram; Elias Delgado; Felipe J. Chaves; Luis Castaño; Alfonso Calle-Pascual; Josep Franch-Nadal; Gemma Rojo-Martínez; et al. (Biomedicines)
Background/Objectives: Although evidence suggests that miR-484 and several fruit components are involved in glucose metabolism and insulin resistance metabolic pathways, the relationship between serum miR-484 levels and fruit consumption in relation to the risk of Type 2 diabetes (T2DM) remains elusive. The aim of this study was to evaluate the possible association between serum miR-484 levels and fruit intake frequency with the risk of T2DM in the Spanish adult population. Methods: 2234 subjects from the Di@bet.es cohort study without T2DM at baseline were studied. Socio-demographic, anthropometric and clinical data were recorded, as well as responses to a questionnaire on habits, including frequency of fruit consumption (daily vs. occasional). T2DM was diagnosed at baseline and after 7.5 years of follow-up. Baseline serum miR-484 levels were measured using real-time qPCR and categorized based on the 25th percentile. Association analyses were performed using logistic regression models adjusted for potential confounders. Interaction effects were evaluated on the multiplicative and additive scales. Results: There was no association between miR-484 levels and fruit intake frequency. Categorized miR-484 levels and fruit consumption were inversely and independently associated with the likelihood of incident T2DM. Analysis of the interaction effect suggests the presence of both positive multiplicative and additive interactions between miR-484 categories and fruit consumption frequency. Conclusions: Our study demonstrates a protective effect of daily fruit intake and high miR-484 levels regarding the risk of T2DM and supports the nutritional recommendations advocating daily fruit consumption. This study also suggests that the combined effect of low miR-484 levels and occasional fruit intake may increase the risk of T2DM beyond their independent effects.